2018
DOI: 10.1007/s12010-018-2783-6
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nonionic Surfactant Adsorption on Enzymatic Hydrolysis of Oil Palm Fruit Bunch

Abstract: Nonionic surfactants have been utilized to improve the enzymatic hydrolysis of lignocellulosic materials. However, the role of surfactant adsorption affecting enzymatic hydrolysis has not been elaborated well. In this work, nonionic surfactants differing in their molecular structures, namely the polyoxyethylene sorbitan monooleate (Tween 80), the secondary alcohol ethoxylate (Tergitol 15-S-9), and the branched alcohol ethoxylate (Tergitol TMN-6), were studied for their effects on the enzymatic hydrolysis of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…for its efficient hydrolysis (Loman and Ju, 2016;Lee et al, 2017;Kane and French, 2018;Sanhueza et al, 2018). Although a number of factors are responsible for lower biomass hydrolysis high cellulase crystallinity, low enzyme accessibility, non-productive enzyme-lignin binding, competitive, and feedback inhibition of the enzyme have been predominantly reported (Agrawal et al, 2015b;Parnthong et al, 2018). Thus, usually a high amount of enzyme is required to achieve high biomass hydrolysis but it negatively affects the commercial viability of the process.…”
Section: Introductionmentioning
confidence: 99%
“…for its efficient hydrolysis (Loman and Ju, 2016;Lee et al, 2017;Kane and French, 2018;Sanhueza et al, 2018). Although a number of factors are responsible for lower biomass hydrolysis high cellulase crystallinity, low enzyme accessibility, non-productive enzyme-lignin binding, competitive, and feedback inhibition of the enzyme have been predominantly reported (Agrawal et al, 2015b;Parnthong et al, 2018). Thus, usually a high amount of enzyme is required to achieve high biomass hydrolysis but it negatively affects the commercial viability of the process.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of nonionic surfactants has been shown to promote enzymatic hydrolysis of lignocellulosic materials and increase sugar release [ 43 , 44 ]. However, this study and regression analysis suggested that the addition of Triton X-100 to enzymatic hydrolysis of untreated rice straw showed no improvement in sugar release.…”
Section: Resultsmentioning
confidence: 99%
“…From the data listed in Table 1, Tergitol TMN-6 has a higher CMC than Tergitol 15-S-9, indicating smaller micellar size. Additionally, Tergitol 15-S-9 has similar hydrocarbon chain length as PKA, but its hydrophilic moiety is larger (Parnthong et al, 2018;Wetchakul, 2013). This causes greater repulsion between Tergitol 15-S-9 head groups and decreases aggregation number as well as size of micelles.…”
Section: Comparison Of Pka Performance With Commercial Nonionic Surfamentioning
confidence: 99%